(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article examines the role of strategic management of consumer decisionmaking in strengthening the competitive position of higher education institutions. In the modern higher education market, universities operate not only as academic organizations but also as service providers that must understand the expectations, needs, and behavioral motives of applicants, students, parents, employers, and other stakeholders. The choice of a higher education institution is increasingly influenced by a combination of academic quality, institutional reputation, tuition affordability, employment prospects, digital services, international cooperation, infrastructure, and the practical value of the degree in the labor market. The article emphasizes that consumer decision-making in higher education should be considered a strategic management issue rather than a narrow marketing task. A higher education institution can strengthen its competitive position when it systematically studies consumer behavior, adapts educational programs to labor market requirements, develops a trustworthy institutional brand, improves student experience, and builds effective communication with target audiences. The study argues that sustainable competitiveness in higher education depends on the ability of universities to create real value for students and to align educational services with social, economic, and professional expectations. The findings of the article show that strategic management of consumer choice contributes to the formation of long-term competitive advantages. These advantages are reflected in improved educational quality, stronger student attraction and retention, better graduate employability, enhanced institutional image, and closer integration with the needs of the labor market. Therefore, higher education institutions should develop consumer-oriented management mechanisms as an essential condition for increasing their competitiveness in a dynamic and increasingly diversified education services market.